Development of a 2D Stop-Motion Animation Titled "Top 10 Scary-Looking but Harmless Animals" to Promote Knowledge and Understanding about Animals - เหลาอ่อน ชมพูนุช; แนวบุตร เกียรติศักดิ์; ดีเจริญชิตพงศ์ จิรวิญญ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research "Development of a 2D Stop Motion Animation: Top 10 Scariest-Looking but Harmless Animals" aims to promote knowledge and understanding of non-venomous animals The objectives are 1) to study and collect information about animals with a scary appearance but are not dangerous to humans 2) to develop and design a 2D Stop Motion animation titled "Top 10 Scariest-Looking but Harmless Animals" to promote understanding of animals and nature and 3) to study the attitudes towards the developed animation and its impact on viewers perception of scary-looking animals and their understanding of coexisting appropriately with animals and nature The sample group consisted of 68 general individuals who were members of a Facebook group for exotic animal lovers and who viewed the 2D Stop Motion animation "Top 10 Scariest-Looking but Harmless Animals" The sample was obtained through accidental random sampling. The results showed that 1) The content quality evaluation by content experts had an overall average score of 4.54 which can be interpreted as being of the highest quality level and 2) The media quality evaluation The content experts gave an overall average score of 3.95 which translates to a high level of quality 3) The satisfaction assessment of the general public members of the Facebook group for exotic animal lovers who viewed the media had an average score of 4.32 which translates to a high level of satisfaction The research results reflect that the media can promote understanding and reduce prejudice towards animals to a significant extent.